Prediction Tool for Parole Breach: Testing the U.S. Salient Factor Score in a Population of Western Australian Parolees. Issue 6 (1st November 2016) - Ferguson, Catherine
Abstract : Parole cancellations inflate prison numbers and increase costs within the criminal justice system as well as the costs to society as a whole. There are a number of tools that predict reoffending, but only a few that are designed specifically for parole cancellation. This research investigated the use of the American tool Salient Factor Score (SFS 81) in a parole sample from Western Australia. Three hundred and sixty completed parole files were examined and scored using the SFS 81 with a criterion of successful completion of parole or a cancellation. The predictor was the SFS 81 score. Receiver operating characteristics (ROC) analysis and logistic regression were used to determine the usefulness of the SFS 81 for the prediction of parole success, and sensitivity and specificity of the SFS 81 were determined. The SFS 81 could be a useful tool for the prediction of parole success in a Western Australian population.